Cytokine expression in spleen affects progression of liver cirrhosis through liver–spleen cross‐talk. Issue 12 (10th February 2014) - Asanoma, Michihito; Ikemoto, Tetsuya; Mori, Hiroki; Utsunomiya, Tohru; Imura, Satoru; Morine, Yuji; Iwahashi, Shuichi; Saito, Yu; Yamada, Shinichiro; Shimada, Mitsuo
Abstract : Aim: It is unclear whether the spleen affects the progression of liver cirrhosis (LC) through "liver–spleen cross‐talk". Transforming growth factor‐β1 (TGF‐β1) is reported to be the most potent cytokine of liver fibrosis, and interleukin‐6 (IL‐6) is an important factor of liver regeneration. In this study, we investigated the expression of cytokines in the spleens of LC patients in order to attempt to prove the existence of liver–spleen cross‐talk. Methods: The study enrolled 22 patients who underwent splenectomy at our institute between 2004 and 2010. TGF‐β1 expression in the resected spleen was measured using immunohistochemical staining. Two‐color immunofluorescent staining for CD68 and TGF‐β1 in the spleen was performed to detect sources of TGF‐β1. IL‐6 expression in the spleen was measured by reverse transcription polymerase chain reaction. Results: TGF‐β1 expression was significantly higher in the spleens of LC patients than in those of patients with normal livers ( P  < 0.05). Coexpression of CD68 and TGF‐β1 was confirmed. The expression of IL‐6 in the spleens of LC patients was significantly lower than that in patients with normal livers ( P  < 0.05). Conclusion: TGF‐β1 produced by macrophages and cytokines such as IL‐6 could affect the progression of liver fibrosis and regeneration in patients with LC via liver–spleen cross‐talk.